Knowledge Marketing: a Postmodern Approach - Augustinaitis, Arūnas (Ekonomika, 2002)
Knowledge is presented in various discourses and in different methodological contexts, as generally reduced to modern and postmodern patterns. The methodological assumptions of knowledge marketing are analyzed and practical orientations concordant with the realities of a knowledge society are formulated. The main purpose is to reveal the distinctions between the classical modern modes of rationalization and the information or knowledge model of rationalization, which the author asserts is based on the conception of legitimative trans-informationality grand discourse. Two types of knowledge identities characterize the market and reflect knowledge transfer in social and professional generalization of knowledge.